Aplikasi Pengolahan Data Penjualan Berbasis Teknologi OLAP - Vilia Meyana (Jurnal Informatika dan Bisnis, 2014)
Information regarding the sales data required by the stakeholders at SWANISH,PT. analysis as a basis for decision-making and strategy determination. On the otherhand, the number of transactional sales data that occur every day cause difficulties in theprocess of analysis and decision making. To overcome these problems, built a datawarehouse and then the results of the data warehouse will be analyzed through a processof OLAP (On-line Analytical Processing). With OLAP, data analysis needs will be easilymet because OLAP capability to display different reports with different dimensions andsuperior operations such as pivoting, drill down, and filtering.